Hubungan Kandungan Informasi Arus Kas, Komponen Arus Kas dan Laba Akuntansi dengan Harga atau Return Saham - Triyono, Jogiyanto Hartono (IAIKAP, 2000)
The Indonesia Institute of Accountants (IAI) published the Statement of Financial Accounting Standard (PSAK) No.2 "Statement of Cash Flows" requires companies to publish the statement of cash flows beginnings from January 1, 1995. The objective of the study is to examine the association of information content of total cash flows, components of cash flows, and accounting income with stock prices or stock returns. Another objective of the study is to compare the predicitve power of between of total cash flows and accounting income with their relation to stock prices or stock returns. As muchas 54 manufacturing firms listed in the Jakarta Stock Exchange (BEJ) were taken as a sample using a purposive sampling method. Data from audited financial satements were taken from Indo0exchange files. The statistics method used to test hypotheses is a linier multiple regression. Two models were considered: levels and return medoles. The multicollinearity test shows that there is no association between independent variables in the regression models, indicating multicillinearity is a serious problem. The heteroscedasticity test shows that variances of disturbances are constant for all observation in independent variables. Therefore, heteroscedasticity is not a problem. Results from diagnostic tests suggest that regression models used in this study are unbiased. The empirical result indicate that disaggregation of total cash flows into their components as required by PSAK No. 2 are significantly associated with stock mandated the publication statement of cash flows. In contrast, the results of the study indicate that total cash flows, components of cash flows, and accounting income are not associated with stock returns in the return model.